Longitudinal research: A panel discussion on conceptual issues, research design, and statistical techniques - WANG, Mo (Institutional Knowledge at Singapore Management University, 2017)
The goal of this article is to clarify the conceptual, methodological, and practical issues that frequently emerge when conducting longitudinal research, as well as in the journal review process. Using a panel discussion format, the current authors address 13 questions associated with 3 aspects of longitudinal research: conceptual issues, research design, and statistical techniques. These questions are intentionally framed at a general level so that the authors could address them from their diverse perspectives. The authors’ perspectives and recommendations provide a useful guide for conducting and reviewing longitudinal studies in work, aging, and retirement research.